Civil-service Pension Schemes Around the World - Palacios, Robert; Whitehouse, Edward (World Bank, Washington, DC, 2014)
There are separate pension schemes for civil servants in about half of the world s countries, including some of the largest developing economies, such as Brazil, China and India. In the higher-income, OECD countries, spending on pensions for public-sector workers makes up one quarter of total pension spending. In less developed countries, this proportion is usually higher. Yet, very little has been written on the design and reform of civil-service pension plans, especially when compared with the voluminous literature on national pension programs. This paper compares civil service pension schemes across countries in terms of benefit provision and cost. We find that in many developing countries, these expenditures are a greater fiscal burden than in higher income countries where the tax base is larger. The paper also compares schemes within the same country covering private sector workers. Finally, we review key policy issues related to pension schemes covering civil servants as well as other public sector workers. In particular, we find that there is little justification for maintaining parallel schemes in the long run.